Barriers to Online Science Learning during the Covid-19 Pandemic in the Dimension of Class Teacher Readiness at Elementary School - Nurjanah, Maya (IJIS Edu : Indonesian Journal of Integrated Science Education, 2022)
Online learning is a new thing in the implementation of the learning process for educators and students. With this online learning, teachers are required to have readiness. A teacher who is ready to learn in any condition will be able to improve the quality of the teacher. In addition, the readiness of a teacher to face the learning process has a major influence on the success of education in schools and teachers who have good readiness will be able to improve student learning. The purpose of this study is to reveal various barriers to online learning during the COVID-19 pandemic in terms of the readiness of classroom teachers in elementary schools. The research method used in this research is using descriptive qualitative research methods. The results of the study show various barriers to online learning from the dimensions of teacher readiness. First, the teacher must think of a strategy on how to get children out of their boredom zone. The second obstacle is that sometimes parents complain that they cannot explain in detail to students. The third obstacle is the signal problem. The fourth obstacle is that sometimes parental assistance is lacking because they have to work from morning to evening. The fifth obstacle is not being able to monitor the process directly. This causes the essence of learning that puts forward the process cannot be observed by the teacher. The product is the only thing the teacher can monitor. The conclusion of this study is that the barriers to online learning in terms of the readiness of classroom teachers in elementary schools are a challenge for teachers. This online learning must be prepared by the teacher as the holder of control in the learning process, because as a facilitator, the teacher must provide facilities that support the learning process, especially in this online learning. This makes teachers required to be technology literate and learn many things, especially online-based learning. This online learning system can be used as a model for further learning